2017
DOI: 10.1186/s12881-017-0392-9
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset of ADCK4 glomerulopathy with renal failure: a case report

Abstract: BackgroundWe present a rare early presentation of a ADCK4-related glomerulopathy. This case is of interest as potentially treatable if genetic results are timely obtained.Case presentationWe report the case of a 5-year-old boy who was identified with significant proteinuria by a urinary routine screening program for school children. Physical examination revealed dysplastic ears and abnormal folded pinna. Albumin level was 41 g/L (39–53 g/L), and urine proteins/creatinine ratio was 2.6 g/g. Renal ultrasound sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…Also, the 2 COQ7 patients described showed peripheral polyneuropathy, again with SNHL and one of them with visual dysfunction(101,102). SNHL is very frequent, especially in COQ6 patients(16/26) (69,71,(107)(108)(109), /74), which generally progressed to ESRD(50,64,110,(112)(113)(114)(115)(116). Onset of SRNS may be before 10 years of age (29/74).Patients with PDSS1 (1/3) (96) and PDSS2 (7/7) (71,97-100)mutations also showed SRNS.…”
mentioning
confidence: 94%
“…Also, the 2 COQ7 patients described showed peripheral polyneuropathy, again with SNHL and one of them with visual dysfunction(101,102). SNHL is very frequent, especially in COQ6 patients(16/26) (69,71,(107)(108)(109), /74), which generally progressed to ESRD(50,64,110,(112)(113)(114)(115)(116). Onset of SRNS may be before 10 years of age (29/74).Patients with PDSS1 (1/3) (96) and PDSS2 (7/7) (71,97-100)mutations also showed SRNS.…”
mentioning
confidence: 94%
“…Additionally, our list of known pathogenic variants may not have included variants detected as part of recent large-scale studies 39 41 , and the fact that some UQ biosynthesis genes were found to be associated with disease earlier than others (e.g., COQ2 was first found in 2006 42 , vs. COQ8B in 2013 29 and COQ7 in 2015 43 ) could have delayed the introduction of some genes into widely used genetic screening panels 44 , meaning that more patients were screened for some genes compared to others. Finally, after the literature review phase of our analysis was concluded, novel pathogenic variants have continued to be described in the clinical literature (e.g., COQ4 45 , COQ6 46 , COQ7 47 , ADCK4 48 , 49 ), indicating that many remain to be reported.…”
Section: Discussionmentioning
confidence: 98%
“…Many signs and symptoms of CoQ10 deficient patients are common among other mitochondrial diseases; these involve multiple organ systems and often show prominent neurologic and myopathic features. However, glomerular dysfunction, such as early-onset FSGS and/or SRNS, is peculiar to CoQ10 deficiencies because of the following mutations: PDSS2 [6,7], COQ2 [8], COQ6 [9,10], and COQ8B [11,12,[19][20][21][22][23][24]. Of four genes, mutation in COQ8B causes selective glomerular phenotype mostly without neurological and myopathic deficits [11,12,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, glomerular dysfunction, such as early-onset FSGS and/or SRNS, is peculiar to CoQ10 deficiencies because of the following mutations: PDSS2 [6,7], COQ2 [8], COQ6 [9,10], and COQ8B [11,12,[19][20][21][22][23][24]. Of four genes, mutation in COQ8B causes selective glomerular phenotype mostly without neurological and myopathic deficits [11,12,[19][20][21][22][23][24]. The age at onset is usually between 5 and 20 years [11,12,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation